Sacral plexus block as a method of intraoperative analgesia - Chaika, G; Dnistrianska, A; Astakhova, O (Pain medicine, 2022)
Despite progress made in anesthesiology and operative gynecology, adequate postoperative analgesia remains un urgent problem. The aim of the work was to evaluate the effectiveness of intraoperative analgesia using an open approach with the use of the sacral protrusion. Plexus block during the operation of extirpation of the uterus leads to a significant decrease in the intensity of the postoperative pain syndrome, the consumption of morphine in the early postoperative period and accelerates the rehabilitation of patients on the first day after operation.